The crucial role of international institutions to tackle child marriage issue - Duarsa, Made Usha M. G.; Yazid, Sylvia (Universitas Airlangga, 2025)
Child marriage is a violation of children’s rights, and it violates international human rights conventions. Its practice remains high globally and has also increased in Nigeria and Indonesia. The efforts given by international institutions to address child marriage issues are certainly not lacking. Nevertheless, child marriage remains persistent in the global landscape. The prevalence of child marriage tends to be based on solid domestic reasons such as cultural and economic factors. This paper argues that the prevalence of child marriage globally occurs because of the absence of strict international policies to form international norms. This situation indicates the diffusion of norms from the international to the domestic level. Thus, the isomorphism theoretical framework is used to clarify the diffusion process of international norms condemning the practice of child marriage. Isomorphism theory explains that international institutions can set normative standards at the global level, which are then passed down to the regional, domestic, and individual levels. With that being said, international institutions play a crucial role in eliminating the implementation of child marriage. The authors used deductive analysis to utilize a structural approach that encourages a systematic explanation of the factors contributing to child marriage. With the existing theoretical framework, deductive analysis is meant to test the accuracy of isomorphism theory through an actual case study of international norm diffusion. Thus, deductive analysis will determine whether the norm diffusion process has been effectively distributed from the international to the individual level.